The incorrect use on tenses in job advertisements - Reny Juliana; Asti Purbarini; Ifan Iskandar (English, 2020)
The research aimed at identifying the types of errors and the frequency of types of errors in using the simple present tense, simple past tense, and simple future tense in job advertisements. The research was qualitative research. The qualitative method used was content analysis. The data of the research were taken from the errors of simple present tense, simple past tense, simple future tense usage in the job advertisements. While the source of data was taken from job advertisements in www.jobstreet.com. There were twenty texts taken as samples. The data analysis used the theory from Ellis that there were several steps in analyzing errors which include collecting data samples, identifying data, describing errors, explaining errors and evaluating error (Ellis, 1994). The result showed that the errors in using simple present tense were higher than in using simple future tense. In the use of simple present tense, there were two errors of auxiliary omission (66,67%), and one (33,33%) error of verb misinformation. In the use of simple past tense, there was zero (0%) error. In the use of simple future tense, there were one (50%) error of verb + ing omission and one error (50%) of verb + ing misinformation. The result of the study can be used as input to avoid further errors.